THE ROLE OF NAHDLATUL ULAMA IN REALIZING THE INDEPENDENCE OF THE UNITED STATE OF THE REPUBLIC OF INDONESIA - Fernando, Dito; Fajar Kurniawan; Muhammad Iqbal Birsyada (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The writing in our article has the following objectives: (1) to explain the beginning of the formation of Nahdlatul Ulama; (2) explaining how Nahdlatul was involved in resisting Dutch colonialism; (3). Explaining the role played by Nahdatlul Ulama in politics (4). Explain the role of Nahdlatul Ulama in the education arena. The method applied in our writing is the historiographic method. The results of this study are known that: (1) Nahdlatul Ulama was formed on January 31, 1929 in Surabaya, more precisely at the residence of Wahab Casbullah. (2) Nahdlatul ulama began to form a network of pesantren to mobilize the strength of Muslims and also educate the students. (3) politics run by Nahdatlul Ulama has populist and state principles, this is what makes Nahdlatul Ulama a religious organization that is based on the common good and interests. (4) Nahdlatul Ulama itself participates in fighting for the independence of the Indonesian nation by educating the nation's children by building Islamic boarding schools and madrasas.